Antibacterial activity of medicinal plants against ESKAPE: An update - Bhatia, Priya (Heliyon, 2021)
Antibiotic resistance has emerged as a threat to global health, food security, and development today. Antibiotic resistance can occur naturally but mainly due to misuse or overuse of antibiotics, which results in recalcitrant infections and Antimicrobial Resistance (AMR) among bacterial pathogens. These mainly include the MDR strains (multi-drug resistant) of ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species). These bacterial pathogens have the potential to “escape” antibiotics and other traditional therapies. These bacterial pathogens are responsible for the major cases of Hospital-Acquired Infections (HAI) globally. ESKAPE Pathogens have been placed in the list of 12 bacteria by World Health Organisation (WHO), against which development of new antibiotics is vital. It not only results in prolonged hospital stays but also higher medical costs and higher mortality. Therefore, new antimicrobials need to be developed to battle the rapidly evolving pathogens. Plants are known to synthesize an array of secondary metabolites referred as phytochemicals that have disease prevention properties. Potential efficacy and minimum to no side effects are the key advantages of plant-derived products, making them suitable choices for medical treatments. Hence, this review attempts to highlight and discuss the application of plant-derived compounds and extracts against ESKAPE Pathogens.